A fake interacting dark energy detection?. Issue 1 (21st October 2020) - Di Valentino, Eleonora; Mena, Olga
ABSTRACT: Models involving an interaction between the dark matter and the dark energy sectors have been proposed to alleviate the long-standing Hubble constant tension. In this paper, we analyse whether the constraints and potential hints obtained for these interacting models remain unchanged when using simulated Planck data. Interestingly, our simulations indicate that a dangerous fake detection for a non-zero interaction among the dark matter and the dark energy fluids could arise when dealing with current cosmic microwave background (CMB) Planck measurements alone. The very same hypothesis is tested against future CMB observations, finding that only cosmic variance limited polarization experiments, such as PICO or PRISM, could be able to break the existing parameter degeneracies and provide reliable cosmological constraints. This paper underlines the extreme importance of confronting the results arising from data analyses with those obtained with simulations when extracting cosmological limits within exotic cosmological scenarios.